An introduction to the New Testament ; v. 1 - Hiebert, D. Edmond (Chicago, IL Moody, 1975)
Contents : v. 1 : The Gospels and Acts. Includes bibliographical references and index.
Keywords: Bible. N.T. Gospels -- introductions; Bible. N.T. Acts -- introductions